2021
DOI: 10.1039/d1ce00785h
|View full text |Cite
|
Sign up to set email alerts
|

Salts, solvates and hydrates of the multi-kinase inhibitor drug pazopanib with hydroxybenzoic acids

Abstract: The marketed formulation of Pazopanib (PAZ) suffers from low and variable bioavailability because of its poor dissolution rate and photostability issues. The drug falls under Biopharmaceutics Classification System (BCS) Class...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…(4) The least-soluble crystals which precipitate from solution could well be a metastable form energetically based on calculations in the gas phase. ( 5) Hydrogen bond strength is directed not only by the acid−base pK a difference but also by the electrostatic potential map 86 at the N acceptor, ancillary hydrogen bonding groups, 87 and proton affinity and pK a equalization. 88 2.3.3.…”
Section: Cocrystal Design Approachesmentioning
confidence: 99%
“…(4) The least-soluble crystals which precipitate from solution could well be a metastable form energetically based on calculations in the gas phase. ( 5) Hydrogen bond strength is directed not only by the acid−base pK a difference but also by the electrostatic potential map 86 at the N acceptor, ancillary hydrogen bonding groups, 87 and proton affinity and pK a equalization. 88 2.3.3.…”
Section: Cocrystal Design Approachesmentioning
confidence: 99%
“…From TG and DSC thermograms, it can be found that S3 , S4 , and S5 are free of solvent/water, while S1 shows an endothermic peak of desolvation at 117 °C, accompanied by weight loss in the range of ∼74–124 °C in the TG curve, and S2 shows a dehydration temperature peak at 137 °C, supported by the mass loss in ∼75–152 °C temperature range in the TG curve. Water and methanol molecules are coming out of crystal lattices at high temperatures above their respective boiling point (78 °C for methanol and 100 °C for water), and this phenomenon can be attributed to strong hydrogen bonds associated with crystalline methanol and water molecules. , S1 , S2 , S4 , and S5 show a similar endothermic peak at ∼178 °C, which might be ascribed to a phase transition. However, it is difficult to estimate the thermodynamic stability relationship of these five forms based on melting points (as an indicator of solid-form stability), according to Burger and Ramberge’s heat of fusion rule, because TMZ–PHBA cocrystals and TMZ pure drugs decompose upon heating.…”
Section: Resultsmentioning
confidence: 99%
“…Water and methanol molecules are coming out of crystal lattices at high temperatures above their respective boiling point (78 °C for methanol and 100 °C for water), and this phenomenon can be attributed to strong hydrogen bonds associated with crystalline methanol and water molecules. 53,54 S1, S2, S4, and S5 show a similar endothermic peak at ∼178 °C, which might be ascribed to a phase transition. However, it is difficult to estimate the thermodynamic stability relationship of these five forms based on melting points (as an indicator of solid-form stability), according to Burger and Ramberge's heat of fusion rule, 55 because TMZ−PHBA cocrystals and TMZ pure drugs decompose upon heating.…”
Section: Mep Analysismentioning
confidence: 87%
“…The CQO and C-O distances in the COO moiety of the COOH group are very close to each other (DD is small), indicative of a carboxylate COO À acceptor. 18 The red shift in the IR stretching frequency (COOH in the coformer to COO À in the binary product; Table S3, ESI †) and the ORTEP plots (Fig. S1, ESI †) confirm the NFPD-FBA adducts as salts.…”
mentioning
confidence: 79%